2007
DOI: 10.1002/ejic.200700872
|View full text |Cite
|
Sign up to set email alerts
|

Optical, Magnetic and Structural Properties of the Spin‐Crossover Complex [Fe(btr)2(NCS)2]·H2O in the Light‐Induced and Thermally Quenched Metastable States

Abstract: Keywords: Iron(II) / Photoswitching / Structural analysis / Photomagnetism / Spin crossover [Fe(btr) 2 (NCS) 2 ]·H 2 O [btr = 4,4Ј-bis(1,2,4-triazole)] is the archetype of highly cooperative and low-dimensional spincrossover complexes, which exhibit low-spin (LS) to highspin (HS) light-induced conversion at very low temperature. The structural reorganizations related to the light-induced and thermally induced LS-HS transitions were characterized by single-crystal X-ray diffraction below the relaxation temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…͑6͔͒ has been argued. 31 It has been observed experimentally, 29 that there exist a high threshold photon density below which no phase change is triggered for ͓Fe͑btr͒ 2 ͑NCS͒ 2 ͔ .H 2 O at 15 K. In our simulations, we observe that indeed for low values of I 0 ͑I 0 Ͻ 0.007͒, no photoconversion occurs; as I 0 increases, the transformation rate increases considerably, and the incubation time shortens ͓Fig. 2͑a͔͒.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…͑6͔͒ has been argued. 31 It has been observed experimentally, 29 that there exist a high threshold photon density below which no phase change is triggered for ͓Fe͑btr͒ 2 ͑NCS͒ 2 ͔ .H 2 O at 15 K. In our simulations, we observe that indeed for low values of I 0 ͑I 0 Ͻ 0.007͒, no photoconversion occurs; as I 0 increases, the transformation rate increases considerably, and the incubation time shortens ͓Fig. 2͑a͔͒.…”
mentioning
confidence: 59%
“…It has been argued that like spin domains ͑LSDs͒ may play a key role in the cooperative spin-transition process, resulting in phase-separation phenomena. Although thermally and photoinduced phase separation has indeed been reported for several SC materials, 25 29 Thermocrystallographic and photocrystallographic experiments have clearly evidenced the presence of LSDs, whose growth kinetics follows the Avrami model. 25,28 We focus hereafter on the photoinduced dynamics of LSD nucleation and growth in the lowtemperature regime using numerical simulation, in close connection with these experimental results.…”
mentioning
confidence: 97%
“…20 This system was selected because of the large optical absorbance of the crystal in the LS state. 24 The available material consisted in lower-quality crystals selected from a batch prepared at Leiden (author J.H.) for previous investigations of polycrystalline samples.…”
Section: Introductionmentioning
confidence: 99%
“…The success of kind experiments consists in in situ laser irradiation of a cryogenically cooled crystal, with a N2 or He gas-flow system for less restricted access than closed cryostat (White et al, 1994), mounted on a diffractometer equipped with a CCD detector for fast data collection (Graafsma et al, 1997;Muchmore, 1999). More recently, Legrand (2005) has developed a crystallographic experimental methodology approach 2007a;2007b) and shown that it is possible to measure with accuracy photo-induced metastable states and to refine its experimental electron density below 35 K using conventional X-ray sources (Legrand et al, 2006;Pillet et al, 2008).…”
Section: State-of-the-art Sample Environments At Laboratoriesmentioning
confidence: 99%